Gambaran Tingkat Pengetahuan Ibu Terhadap Ikterus Fisiologi Pada Bayi Baru Lahir Di Bpm Sri Wahyuni - Indrianita, Vivin
Infant Mortality Rate is total baby death in the 28 days baby first life 1000 life births.  The most common caused by death perinatal  is complication when pregnancy and complication during labour such as asphyxia, sepsis, infant low birt wight and icterus neonatorum. Icterus is one of similar disease found on liver on newborn baby because of the hiperbilirubin.This was descriptive research conducted at BPM Sri Wahyuni, Amd, Keb. Kwangsang sedati sidoarjo on juni to juli 2017, sample in this research counted 30 respondents, this research used questionare paper, this used single variable that is maternal knowledge level about physiological icterus in newborn baby.The research shown from 30 respondent, 2 respondent had good knowledge (6,7%), 6 respondent (20%) had sufficient knowledge, and 22 respondent (73,3%) had less knowledge. Base on the research result it was suggested to individual approarch and health education about icterus symptom and hendling due to icterus physiological.